Role of Iodine Recycling on Sea‐Salt Aerosols in the Global Marine Boundary Layer - Li, Qinyi; Tham, Yee Jun; Fernandez, Rafael P.; He, Xu‐Cheng; Cuevas, Carlos A.; Saiz‐Lopez, Alfonso (Geophysical research letters, 2022)
Heterogeneous uptake of hypoiodous acid (HOI), the dominant inorganic iodine species in the marine boundary layer (MBL), on sea‐salt aerosol (SSA) to form iodine monobromide and iodine monochloride has been adopted in models with assumed efficiency. Recently, field measurements have reported a much faster rate of this recycling process than previously assumed in models. Here, we conduct global model simulations to quantify the range of effects of iodine recycling within the MBL, using Conventional, Updated, and Upper‐limit coefficients. When considering the Updated coefficient, iodine recycling significantly enhances gaseous inorganic iodine abundance (∼40%), increases halogen atom production rates (∼40% in I, >100% in Br, and ∼60% in Cl), and reduces oxidant levels (−7% in O3, −2% in OH, and −4% in HO2) compared to the simulation without the process. We appeal for further direct measurements of iodine species, laboratory experiments on the controlling factors, and multiscale simulations of iodine heterogeneous recycling. Plain Language Summary The interaction between ocean and atmosphere affects atmospheric chemistry and the climate system. Due to the technical difficulties in direct measurements in the open ocean and coastal environments, the understanding of the marine atmosphere has been heavily dependent on the utilization of multiscale models with limited observational constraints. The development in instrumentation facilitates the direct observation of previously undetected species and unquantified parameters calling for updates of atmospheric models and revisions of the role of relevant processes. Reactive halogen (chlorine, bromine, and iodine) chemistry plays a vital role in controlling the atmospheric composition and oxidation in the marine environment. In particular, iodine chemistry dominates the halogen effects in the marine boundary layer and hypoiodous acid (HOI) is the most abundant iodine species. Recently, field evidence shows that the heterogeneous recycling of iodine is much faster than previously assumed. Here we update a global model with larger coefficients and revisit the role of the HOI heterogeneous processing in marine atmospheric chemistry. These results indicate that the substantial effect of iodine heterogeneous recycling on iodine partitioning, halogen recycling, and oxidant budget may have been underestimated in previous studies and in current models. Key Points Heterogeneous recycling of iodine on sea‐salt aerosol leads to large changes in iodine level and partitioning in the global MBL Iodine recycling substantially enhances the production rates of halogen atoms and reduces the levels of oxidants Effect of iodine recycling is very sensitive to the uptake efficiency and its range is explored using recently reported coefficients